Perlindungan Hukum Bagi Pemberi Gadai Dalam Transaksi Lelang Emas Objek Gadai: (Studi di PT. Pegadaian UPC Midang) - Annisa Balqist; H. Zaenal Arifin Dilaga (Private Law, 2022)
This study aimed to determine the procedure for implementing the gold auction transaction for the object of pawn and legal protection for the pawnbroker in the gold auction transaction for the object of the pawn at PT. UPC Midang Pawnshop. This study of this research used normative-empirical legal study methods with a statutory approach, a conceptual, and a sociological. Based on the research results, the procedure for implementing the gold auction transaction for pawned objects at PT. UPC Midang Pawnshop went through three stages, namely: Pre-auction procedures, Auction implementation procedures, and Post-auction procedures. The legal protection for the pawnbroker in the gold auction transaction for the object of the pawn was based on the Civil Code, The Consumer Protection Act, Moreover, the legal protection provided by PT. UPC Midang Pegadaian.